Likuiditas, Profitabilitas Dan Solvabilitas Dalam Peningkatan Pertumbuhan Laba Pada Perusahaan Industri Barang Konsumsi - Indriyana Widyastuti; Abdul Halik; Siti Mujanah (Excellent, 2025)
This study aims to determine whether the current ratio, return on assets, and debt to equity ratio can simultaneously and simultaneously increase profit growth. This type of research is quantitative research. The sample used in this study consists of 19 consumer goods industry sector companies listed on the Indonesia Stock Exchange with a research observation period of 5 years, so the number of samples in this study is 95. The sampling method uses a purposive sampling method. The data analysis methods used in this study include descriptive statistics, hypothesis testing (multiple linear regression analysis, t-test, F-test and analysis of the coefficient of determination (R2)). Based on the results of the simultaneous testing, the debt to equity ratio variable can significantly increase profit growth, while the current ratio and return on assets variables cannot significantly increase profit growth. Based on the results of simultaneous testing, it shows that the independent variables (current ratio, return on assets and debt to equity ratio) can jointly increase profit growth.